Potential Antibiotic-Drug Interactions: Analysis of Pediatric Patient Prescriptions at Omnia Farma Pharmacy Purwokerto - Utami, Esti Dyah; Maharani, Farah Ayu; Ekowati, Heny; Suryoputri, Masita Wulandari (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2026)
Background: The use of drugs in pediatric patients requires special attention because pediatrics have physiological and anatomical differences with adults. Children are more susceptible to infectious diseases and often get antibiotic therapy and other symptomatic drugs to support recovery, thus increasing the potential for drug interactions.Objectives: The study aimed to analyze the incidence of potential antibiotic drug interactions prescribed to pediatric patients at Omnia Farma Pharmacy Purwokerto. Methods: This observational study was conducted retrospectively by collecting prescription data of pediatric patients aged 0-18 years at Omnia Farma Pharmacy Purwokerto from January to December 2023 using a simple random sampling method. Data were analyzed descriptively using the standard of the Lexicomp Interaction Checker database and other scientific literature. Results: There were 286 patient prescriptions that met the inclusion criteria. The majority of patients were male, aged 1-5 years, with the most prescribed antibiotic being amoxicillin (73.13%). The study only found potential drug interactions in 12 antibiotic prescriptions (4.20%), of which 50% were interactions between azithromycin and salbutamol. Most of the potential antibiotic-drug interactions found were of minor severity (91.67%), with pharmacodynamic interaction mechanisms (83.33%).Conclusion: The antibiotic prescriptions given to pediatric patients at Omnia Farma Pharmacy were quite good in terms of the minimal number of potential drug interactions found. Special attention to the therapy of pediatric patients through the collaboration of doctors and pharmacists is important to help patients get optimal therapy.